PENGARUH KEPEMIMPINAN DAN KEMAMPUAN KERJA TERHADAP KINERJA DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING PADA LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA (LPP RRI) PADANG - Syaifora, Loveana; Indarti, Sri; Maulida, Yusni (Jurnal Tepak Manajemen Bisnis, 2018)
This study aimed to examine and analyze the influence of leadership andwork ability on performance with commitment as intervening variable. The studywas conducted in LPP RRI Padang.The data used consist of primary and secondary data. Data were collected byusing questionnaires that given to 108 employees of LPP RRI Padang that usedCensus Sample. Descriptive analysis method is used to describe thecharacteristics of respondents and the research hyphotheses by using relevantstatistical tests. Variables used are leadership and work ability as independentvariable, performance as dependent variable and commitment to intervening ormediation variable. Analyzer used is path analysis by using program of SPSS 21for windows.The results of this study conclude that leadership has a direct influencesignificantly on performance, the work ability directly influence significantly toperformance and commitment have a significant effect on performance. Indirectly,commitment has positive mediation role on the influence of leadership onperformance and commitment has a positive mediation role on the influence ofwork ability on performance. The improvement of leadership effectiveness) andwork ability are recommended in order to optimize employee performance andcommitment.